Semiotic Analysis on Indomie Advertisement “Bareng Indomie Kuah, Bikin Kuahlity Time Gak Tergantikan” : Penelitian - Rinda Riztya; Sesilia Krisfianti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Advertising is a communication medium that has an important role in shaping people's views on a product. One method that can be used to analyze the meaning in advertisements is Roland Barthes's semiotics, which divides signs into two levels of meaning, namely denotation and connotation, and reveals the myths contained in them. This research aims to analyze the semiotic signs in the Indomie advertisement titled “Bareng Indomie Kuah, Bikin Kuahlity Time Gak Tergantikan” uploaded on YouTube. The research method used is descriptive qualitative with Roland Barthes' semiotic approach. Data were obtained through visual and verbal analysis in the ad, which were then categorized based on denotative, connotative, and mythical elements contained in the advertisement. The results show that this advertisement not only promotes Indomie products, but also builds an image of togetherness, warmth, and precious moments when consuming the product together. The myth formed in this advertisement is that Indomie is not just an instant food, but also a symbol of togetherness and warmth in Indonesian families.